São Francisco: o rio pelo seu povo - Lamas, Maria Aparecida da Silva (2013)
This research aims at analysing the discourse of ribeirinha communities located across São Francisco River in order to identify patterns of beliefs and social values. Who are the people living riverside? Which social realities bound them together? Which representations build the society they are in? The language choices made when we are part of a given discourse are not arbitrary; they are filled with the speaker s identity, her meanings and beliefs. The theoretical background of this research lies on the Systemic Functional-Linguistics (Halliday, 1994, 2004), since the analysis carried on focuses on the System of Transitivity. Here we address the corpus from a perspective which recognizes language as a social phenomenon, since this study establishes a dialogue with other areas such as anthropology, sociology and cultural studies. The research corpus is a number of interviews collected in ribeirinha communities across São Francisco riverside, taken from 2005 through 2008 by the photojournalist João Zinclar. The interviews took place in communities which were located in the five states which border the river, at the time was the controversy over the transposition of the water from the river. The analysis revealed a strong sense of sense of community by the ribeirinhos. It has also shown a strong feeling of proud, result of the fact they are part of a social/ethnic group (Indians, quilombola etc.). Their territory the riverside is responsible for mediating the relationship across the many communities. On the other hand, it was clear such communities are suffering deterritorialization, losing the place where they affective and symbolic values were conceived. This has created a great feeling of anguish and distress felt by the ribeirinha communities and resulting in situations of social conflict